2023
DOI: 10.3389/fmicb.2023.1259133
|View full text |Cite
|
Sign up to set email alerts
|

Dietary taurine effect on intestinal barrier function, colonic microbiota and metabolites in weanling piglets induced by LPS

Dong-dong Zhao,
Ye-dan Gai,
Chen Li
et al.

Abstract: Diarrhea in piglets is one of the most important diseases and a significant cause of death in piglets. Preliminary studies have confirmed that taurine reduces the rate and index of diarrhea in piglets induced by LPS. However, there is still a lack of relevant information on the specific target and mechanism of action of taurine. Therefore, we investigated the effects of taurine on the growth and barrier functions of the intestine, microbiota composition, and metabolite composition of piglets induced by LPS. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
2
0
0
Order By: Relevance
“…In line with our results, Jiajun Yang et al demonstrated that probiotic L. salivarius increased arginine and proline production, consequently enhancing pigs' nutritional digestion, absorption, and immunity [71]. Similarly, the taurine metabolism may regulate oxidative damage and inflammation in intestinal infections [83]. In our study, 3, 9, 5, 7, and 3 DEM pathways were found in valine, leucine, and isoleucine biosynthesis, the protein digestion and absorption pathway, the arginine and proline metabolism, amino acid biosynthesis, and the taurine and hypo-taurine metabolism, respectively (Figures S9A-C and S10A,B).…”
Section: Discussionsupporting
confidence: 90%
“…In line with our results, Jiajun Yang et al demonstrated that probiotic L. salivarius increased arginine and proline production, consequently enhancing pigs' nutritional digestion, absorption, and immunity [71]. Similarly, the taurine metabolism may regulate oxidative damage and inflammation in intestinal infections [83]. In our study, 3, 9, 5, 7, and 3 DEM pathways were found in valine, leucine, and isoleucine biosynthesis, the protein digestion and absorption pathway, the arginine and proline metabolism, amino acid biosynthesis, and the taurine and hypo-taurine metabolism, respectively (Figures S9A-C and S10A,B).…”
Section: Discussionsupporting
confidence: 90%
“…of gut microbiota composition and enhancing tight junction proteins, thereby reducing gut permeability [37][38][39][40]. In accordance, we found that plasma taurine levels were negatively correlated with gut-derived metabolites, such as TMAO, quinolinic acid, and phenylacetic acid in PCC patients during convalescence.…”
Section: Plos Onesupporting
confidence: 81%